Christmas vendetta [large type] - Hansen, Valerie (Hansen, Valerie, Emergency responders., 2021)
"Sandy Lynn Forrester's Christmas holiday takes a terrifying turn when someone breaks into her home and attacks her roommate...thinking it's her. But no one believes that an imprisoned man from Sandy Lynn's past is behind the attacks -- except for her high school heartbreak, ex-cop Clay Danforth. Can she trust Clay to keep her safe in the Ozark wilderness long enough to stop a ruthless criminal's vengeance?"--Page [4] cover.